Logiques autoritaires et transformation démocratique en Tunisie: le cas du président de l’Assemblée des Représentants du Peuple (2014-2019) - Mohamed Limam (L’Année du Maghreb)
The staff of the former regime endorsed an important role in the process of democratic transformation launched since 2011 in Tunisia. Mohamed Ennaceur , who is colleague and partner to Beji Caied Essebsi (elected President of the Republic in 2014), was elected President of the Assembly of Representatives of the People. Comparative political experience shows that democratic consolidation depends, among other things, on the disposition of the major players representing the former regime to respect the rules of the democratic game. On the basis of this observation, we assume that politicians present in the authoritarian regime, through retaining a key position in the machinery of the State, tend to seize new institutional tools and use them for their benefit. We formulate the hypothesis that Mohamed Ennaceur introduced practices, with President Béji Caïd Essebsi, which were in clear violation of the Constitution and the rules which manage the functioning of the institutions, as defined by the 2014 Constitution. Indeed, the way he managed various conflicts is a sign that on difficult issues, Mohamed Ennaceur was not rid of his authoritarian habitus.